Flame-retardant ABS composite material for automobile and preparation method thereof

Through reasonable proportioning and processing technology, flame-retardant ABS composite materials for automobiles with excellent flame retardant, antibacterial, waterproof and UV aging resistance were prepared, which solved the shortcomings of existing materials in antibacterial, waterproof and UV aging resistance.

CN119842182AActive Publication Date: 2025-04-18SHENZHEN CHENYUFENG ENG PLASTIC NEW MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510083780.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-18
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The existing flame-retardant ABS composite materials for automobiles have shortcomings in antibacterial properties, waterproof properties and UV aging resistance, resulting in poor antibacterial durability, antibacterial instability, and reduced impact strength under ultraviolet irradiation.

Method used

By reasonably proportioning ABS resin, bromine flame retardant, silica, lubricant, additive, synergist and antioxidant, intensive refinery and twin screw extrusion granulation, flame retardant ABS composite materials for automobiles with excellent flame retardant properties, cantilever beam notch impact strength, UV aging resistance and waterproofing properties were prepared.

Benefits of technology

It realizes the long-term antibacterial properties of ABS composite materials, improves antibacterial properties, enhances waterproof properties and improves UV aging resistance, ensuring the stable performance of the material under different environmental conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a flame-retardant ABS composite material for an automobile and a preparation method of the flame-retardant ABS composite material. The flame-retardant ABS composite material for the automobile comprises the following raw material components in parts by weight: 50-80 parts of ABS resin, 6-15 parts of a brominated flame retardant, 3-5 parts of silicon dioxide, 1-3 parts of a lubricant, 1-4 parts of an auxiliary agent, 4-7 parts of a synergist and 1-2 parts of an antioxidant. The invention also provides a preparation method of the flame-retardant ABS composite material for the automobile, and the flame-retardant ABS composite material for the automobile is prepared by mixing and melting the raw material components, extruding by a twin-screw extruder and granulating. Compared with the prior art, the ABS composite material prepared by the invention not only has excellent flame retardant property, but also has better cantilever beam notch impact strength, ultraviolet aging resistance and waterproofness, meanwhile, the antibacterial property of the ABS composite material is also improved, and long-acting antibacterial property is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a flame-retardant ABS composite material for automobiles and a preparation method thereof. Background Art

[0002] ABS (Acrylonitrile Butadiene Styrene) resin refers to acrylonitrile-butadiene-styrene copolymer, which is a thermoplastic polymer material with high strength, good toughness and easy processing and molding. It is widely used in automobiles, home appliances, machinery, textiles and other industries. In recent years, with the continuous improvement of the lightweight level of automobiles, ABS is often used to manufacture automobile parts, such as dashboards, body panels, interior panels, steering wheels, sound insulation panels, door locks, bumpers, ventilation ducts, etc., and the demand for ABS resin in the automobile industry has increased rapidly. However, due to the many possible fire sources inside the car, such as sparks generated by electrical system failures, many countries and regions have formulated strict flame retardant standards for automobile interior materials for safety reasons. Therefore, flame retardant ABS composite materials with good flame retardant properties are needed to manufacture automobile interior and some exterior parts.

[0003] CN106589771A discloses a method for preparing highly flame-retardant ABS automotive interior parts. The flame-retardant ABS plastic prepared by the invention has good flame retardancy and is used to make automotive interior parts with reliable quality and good safety. Flame-retardant materials for automotive interior parts include automotive ceiling fabrics, automotive carpets, trunk blankets, trunk side trims, wheel cover blankets, etc. However, the highly flame-retardant ABS automotive interior parts formed by the flame-retardant ABS plastic provided by the invention have average antibacterial and waterproof properties, resulting in poor antibacterial durability of the product, unstable antibacterial properties, and significantly reduced stability of the product's water washing performance, further limiting the use efficiency of the product.

[0004] CN118931100A discloses a heat-resistant ABS composite material for automobiles and a preparation method thereof. The heat-resistant ABS composite material for automobiles comprises the following raw materials in parts by weight: 80-90 parts of ABS resin, 10-20 parts of thermoplastic polyurethane, 10-20 parts of modified filler, 5-15 parts of silicone foam microspheres, 0.1-1 parts of lubricant, 0.1-1 parts of antioxidant, 1-2 parts of flame retardant, and 3-8 parts of mixed fiber. The ABS composite material provided by the invention has the advantages of strong heat resistance and good fluidity, is not easy to produce internal stress and crack during injection molding, and has strong impact resistance, but the ABS composite material has poor resistance to ultraviolet light aging. The automobile exterior parts (such as bumpers, body panels, etc.) prepared by using the ABS composite material are exposed to outdoor environments for a long time. Due to the effect of ultraviolet rays, their impact strength will gradually decrease over time and are easily damaged when they are hit. Summary of the invention

[0005] In view of the above-mentioned defects of the prior art, the present invention provides a flame-retardant ABS composite material for automobiles and a preparation method thereof. The ABS composite material prepared by the present invention not only has excellent flame retardancy, but also has good Izod notched impact strength, anti-ultraviolet light aging performance and waterproof performance, and at the same time improves the antibacterial performance of the ABS composite material, achieving long-term antibacterial performance.

[0006] To achieve the above object, the present invention provides a method for preparing a flame-retardant ABS composite material for automobiles, comprising the following steps: (1) Mix ABS resin, brominated flame retardant, lubricant, additive, antioxidant, silicon dioxide and synergist to obtain a mixture; then add the mixture into an internal mixer at a mixing temperature of 100-150° C. for 15-30 minutes to obtain a premix; (2) The premix is ​​then fed into a twin-screw extruder for extrusion and granulation. The screw speed of the twin-screw extruder is 300-800 rpm and the barrel temperature is 160-220° C., thereby obtaining a flame-retardant ABS composite material for automobiles.

[0007] Preferably, the weight ratio of each raw material component is: ABS resin 50-80 parts, brominated flame retardant 6-15 parts, silicon dioxide 3-5 parts, lubricant 1-3 parts, auxiliary agent 1-4 parts, synergist 4-7 parts, antioxidant 1-2 parts.

[0008] Preferably, the brominated flame retardant is selected from one or more of decabromodiphenylethane, brominated epoxy resin, tetrabromobisphenol A, and bromotriazine.

[0009] Preferably, the lubricant is selected from one or more of pentaerythritol stearate, paraffin, silicone powder, and ethylene bis stearamide; The auxiliary agent is prepared by mixing epoxy soybean oil and epoxy modified silicone oil in a mass ratio of 1:1-3.

[0010] Preferably, the antioxidant is selected from one or more of antioxidant 1076, antioxidant 1010, antioxidant 168, antioxidant 3114, and antioxidant 1098.

[0011] Preferably, the preparation method of the synergist comprises the following steps, measured by weight: S1. Mix 4-6 parts of nano-hydroxyapatite with 95-105 parts of ethanol, and then ultrasonically treat for 20-40 minutes to obtain a suspension; add 1-3 parts of lacquer phenol to the suspension, mix and stir at 65-75°C for 2-4 hours to obtain a mixed solution; centrifuge the mixed solution, collect the precipitate, wash it with ethanol 2-3 times, and dry it at 43-48°C for 3-6 hours to obtain modified nano-hydroxyapatite; then add 1-3 parts of modified nano-hydroxyapatite to 45-55 parts of a copper chloride aqueous solution with a concentration of 0.8-1.5 g / L, and add 0.01-0.05 parts of anhydrous sodium acetate, and then mix and stir at 10-20 MPa and 80-100°C for 3-5 hours; centrifuge after cooling, collect the precipitate, wash it with ethanol 1-2 times, then wash it with water 2-3 times, and dry it at 40-48°C for 8-15 hours to obtain modified nano-hydroxyapatite loaded with an antibacterial agent; S2. Mix 8-12 parts of starch additive and 1-3 parts of antibacterial agent-modified nano-hydroxyapatite prepared in step S1 with 95-105 parts of water, and then stir at 38-42° C. and 200-400 rpm for 2-4 hours, and then centrifuge at 2000-5000 rpm for 3-8 minutes, collect the precipitate, wash it with water 2-3 times, and dry it at 43-48° C. for 30-60 minutes to obtain a synergist.

[0012] Preferably, the starch additive in step S2 is selected from at least one of porous starch and modified porous starch.

[0013] Preferably, the preparation method of the modified porous starch comprises the following steps, measured by weight: 0.5-1.5 parts of anhydrous sodium sulfate and 0.05-0.2 parts of sodium hydroxide are added to 95-105 parts of water and mixed evenly, then 4.5-5.5 parts of porous starch and 0.3-0.5 parts of modifier are added, and the mixture is stirred at 40-60°C for 2-5 hours; then the pH value is adjusted to 5.8-6.2 with 0.5-1 mol / L hydrochloric acid aqueous solution, filtered, the precipitate is collected, washed with water for 2-3 times, and then washed with 90-95wt% ethanol aqueous solution for 2-3 times, and dried at 38-45°C for 8-12 hours to obtain modified porous starch.

[0014] More preferably, the modifier is selected from benzyl iodide, benzyl bromide, and 1,4-dichlorobenzyl.

[0015] The present invention also provides a flame-retardant ABS composite material for automobiles, which is prepared by the above method.

[0016] Beneficial effects of the present invention: 1. Compared with the prior art, the present invention mixes and melts ABS resin, bromine flame retardant, silicon dioxide, lubricant, auxiliary agent, synergist and antioxidant in a reasonable proportion, and prepares flame-retardant ABS composite material for automobile by extrusion and granulation. ABS resin is selected as the matrix of the composite material to provide basic mechanical properties and processing properties for the material. At the same time, bromine flame retardant bromotriazine is introduced as the main flame retardant component, which effectively improves the flame retardant properties of the composite material. Pentaerythritol stearate plays the role of lubrication and demoulding, which is conducive to improving the processing properties of ABS composite material and helping to ensure the surface quality of the finished product. Silicon dioxide can be used as a reinforcing agent to improve the strength and hardness of the composite material and enhance the mechanical properties of the material. At the same time, it can also improve the heat resistance and dimensional stability of the material to a certain extent, so that the material maintains good performance under different environmental conditions. The introduction of antioxidant can effectively inhibit the occurrence of oxidation reaction, prevent the material from being degraded and aged due to oxidation, extend the service life of the material, and maintain the performance stability of the material.

[0017] 2. The present invention selects epoxy soybean oil and epoxy-modified silicone oil as auxiliary agents. Epoxy soybean oil has a good plasticizing effect, which can increase the flexibility of the composite material, reduce its brittleness, and improve the impact resistance of the material; epoxy-modified silicone oil not only has a certain plasticizing effect, but also can improve the surface properties of the material, can make the surface of the composite material smoother, and improve the weather resistance and stability of the material to a certain extent. In addition, the introduction of epoxy soybean oil and epoxy-modified silicone oil can also interact with silicon dioxide through chemical bonding and physical adsorption, and interact with ABS resin through chemical reaction and physical action, thereby effectively improving the compatibility between silicon dioxide and ABS resin, which is conducive to improving the overall performance of ABS composite materials.

[0018] 3. Compared with the prior art, the present invention prepares a synergist by mixing modified porous starch and modified nano-hydroxyapatite loaded with an antibacterial agent, and introduces the synergist into an ABS resin matrix to prepare a flame-retardant ABS composite material for automobiles, which is beneficial to enhancing the cantilever beam notched impact strength, anti-ultraviolet light aging performance and waterproof performance of the ABS composite material, while also improving the antibacterial performance of the ABS composite material to achieve long-term antibacterial performance. DETAILED DESCRIPTION

[0019] Parameters for specific chemical substances used, sources.

[0020] ABS resin, grade: 0215H, brand: Jilin Petrochemical; Nanohydroxyapatite, average particle size: 20 nm, from Beijing Dekedaojin Technology Co., Ltd.; Silicon dioxide, average particle size: 5 μm; Epoxidized soybean oil, CAS No.: 8013-07-8, from Nantong Runfeng Petrochemical Co., Ltd.; Epoxy modified silicone oil, brand: DY-E701, from Shandong Dayi Chemical Co., Ltd.; Urushiol, CAS No.: 35237-02-6; The preparation method of porous starch includes the following steps: dispersing a corn starch solution in a sodium acetate buffer solution with a pH of 5.5 to obtain a 30% (w / w) starch milk, then adding 2% (w / w) complex enzyme (α-amylase: saccharifying enzyme = 1:2), incubating at 50°C for 6 hours, then adjusting the pH to 3.0 to neutralize the system and incubating for 15 minutes; the system is centrifuged at 4000r / min and washed 3 times with deionized water, and the finally obtained sample is dried at 40°C and passed through a 100-mesh sieve, and stored for later use.

[0021] Example 1 A method for preparing a flame-retardant ABS composite material for automobiles comprises the following steps: (1) 75 parts by weight of ABS resin, 8 parts by weight of bromotriazine, 2 parts by weight of pentaerythritol stearate, 3 parts by weight of auxiliary agent, 1.5 parts by weight of antioxidant 1010, 4 parts by weight of silicon dioxide and 5 parts by weight of synergist are mixed uniformly to obtain a mixture; then the mixture is added to an internal mixer at a mixing temperature of 120° C. for 25 minutes to obtain a premix; (2) The premix is ​​then fed into a twin-screw extruder for extrusion and granulation. The screw speed of the twin-screw extruder is 500 rpm and the barrel temperature is 190°C, thereby obtaining a flame-retardant ABS composite material for automobiles.

[0022] The auxiliary agent is prepared by mixing epoxy soybean oil and epoxy modified silicone oil in a mass ratio of 1:2.

[0023] The preparation method of the synergist comprises the following steps: S1. Mix 5 parts by weight of nano-hydroxyapatite with 100 parts by weight of ethanol, and then ultrasonically treat for 30 minutes to obtain a suspension; add 2 parts by weight of lacquer phenol to the suspension, mix and stir at 70°C for 3 hours to obtain a mixed solution; centrifuge the mixed solution, collect the precipitate, wash it with ethanol 3 times, and dry it at 45°C for 5 hours to obtain modified nano-hydroxyapatite; then add 2 parts by weight of modified nano-hydroxyapatite to 50 parts by weight of a 1 g / L copper chloride aqueous solution, and add 0.03 parts by weight of anhydrous sodium acetate, and then mix and stir at 12 MPa and 90°C for 4 hours; centrifuge after cooling, collect the precipitate, wash it with ethanol twice, then wash it with water 3 times, and dry it at 45°C for 12 hours to obtain modified nano-hydroxyapatite loaded with an antibacterial agent; S2. Mix 10 parts by weight of porous starch and 2 parts by weight of the antibacterial agent-modified nano-hydroxyapatite prepared in step S1 with 100 parts by weight of water, and then stir at 40°C and 300 rpm for 3 hours, and then centrifuge at 4000 rpm for 5 minutes, collect the precipitate, wash it with water 3 times, and dry it at 45°C for 40 minutes to obtain a synergist.

[0024] Example 2 A method for preparing a flame-retardant ABS composite material for automobiles, which is different from Example 1 in that the method for preparing the synergist comprises the following steps: S1. Mix 5 parts by weight of nano-hydroxyapatite with 100 parts by weight of ethanol, and then ultrasonically treat for 30 minutes to obtain a suspension; add 2 parts by weight of lacquer phenol to the suspension, mix and stir at 70°C for 3 hours to obtain a mixed solution; centrifuge the mixed solution, collect the precipitate, wash it with ethanol 3 times, and dry it at 45°C for 5 hours to obtain modified nano-hydroxyapatite; then add 2 parts by weight of modified nano-hydroxyapatite to 50 parts by weight of a 1 g / L copper chloride aqueous solution, and add 0.03 parts by weight of anhydrous sodium acetate, and then mix and stir at 12 MPa and 90°C for 4 hours; centrifuge after cooling, collect the precipitate, wash it with ethanol twice, then wash it with water 3 times, and dry it at 45°C for 12 hours to obtain modified nano-hydroxyapatite loaded with an antibacterial agent; S2. Mix 10 parts by weight of the modified porous starch and 2 parts by weight of the antibacterial agent-loaded modified nano-hydroxyapatite prepared in step S1 with 100 parts by weight of water, and then stir the mixture at 40°C and 300 rpm for 3 hours, and then centrifuge at 4000 rpm for 5 minutes, collect the precipitate, wash it with water 3 times, and dry it at 45°C for 40 minutes to obtain a synergist.

[0025] The preparation method of the modified porous starch comprises the following steps: 1 part by weight of anhydrous sodium sulfate and 0.1 part by weight of sodium hydroxide were added to 100 parts by weight of water and mixed evenly, and then 5 parts by weight of porous starch and 0.4 parts by weight of 1,4-dichlorobenzyl were added, and the mixture was stirred at 50°C for 3 hours; then the pH was adjusted to 6 with a 1 mol / L hydrochloric acid aqueous solution, filtered, the precipitate was collected, washed 3 times with water, and then washed 3 times with a 90wt% ethanol aqueous solution, and dried at 40°C for 10 hours to obtain a modified porous starch.

[0026] Example 3 A method for preparing a flame-retardant ABS composite material for automobiles, which is different from Example 1 in that the method for preparing the synergist comprises the following steps: S1. Mix 5 parts by weight of nano-hydroxyapatite with 100 parts by weight of ethanol, and then ultrasonically treat for 30 minutes to obtain a suspension; add 2 parts by weight of lacquer phenol to the suspension, mix and stir at 70°C for 3 hours to obtain a mixed solution; centrifuge the mixed solution, collect the precipitate, wash it with ethanol 3 times, and dry it at 45°C for 5 hours to obtain modified nano-hydroxyapatite; then add 2 parts by weight of modified nano-hydroxyapatite to 50 parts by weight of a 1 g / L copper chloride aqueous solution, and add 0.03 parts by weight of anhydrous sodium acetate, and then mix and stir at 12 MPa and 90°C for 4 hours; centrifuge after cooling, collect the precipitate, wash it with ethanol twice, then wash it with water 3 times, and dry it at 45°C for 12 hours to obtain modified nano-hydroxyapatite loaded with an antibacterial agent; S2. Mix 10 parts by weight of the modified porous starch and 2 parts by weight of the antibacterial agent-loaded modified nano-hydroxyapatite prepared in step S1 with 100 parts by weight of water, and then stir the mixture at 40°C and 300 rpm for 3 hours, and then centrifuge at 4000 rpm for 5 minutes, collect the precipitate, wash it with water 3 times, and dry it at 45°C for 40 minutes to obtain a synergist.

[0027] The preparation method of the modified porous starch comprises the following steps: 1 part by weight of anhydrous sodium sulfate and 0.1 part by weight of sodium hydroxide were added to 100 parts by weight of water and mixed evenly, and then 5 parts by weight of porous starch and 0.4 parts by weight of benzyl bromide were added, and the mixture was stirred at 50°C for 3 hours; then the pH was adjusted to 6 with a 1 mol / L hydrochloric acid aqueous solution, filtered, the precipitate was collected, washed 3 times with water, and then washed 3 times with a 90wt% ethanol aqueous solution, and dried at 40°C for 10 hours to obtain modified porous starch.

[0028] Example 4 A method for preparing a flame-retardant ABS composite material for automobiles, which is different from Example 1 in that the method for preparing the synergist comprises the following steps: S1. Mix 5 parts by weight of nano-hydroxyapatite with 100 parts by weight of ethanol, and then ultrasonically treat for 30 minutes to obtain a suspension; add 2 parts by weight of lacquer phenol to the suspension, mix and stir at 70°C for 3 hours to obtain a mixed solution; centrifuge the mixed solution, collect the precipitate, wash it with ethanol 3 times, and dry it at 45°C for 5 hours to obtain modified nano-hydroxyapatite; then add 2 parts by weight of modified nano-hydroxyapatite to 50 parts by weight of a 1 g / L copper chloride aqueous solution, and add 0.03 parts by weight of anhydrous sodium acetate, and then mix and stir at 12 MPa and 90°C for 4 hours; centrifuge after cooling, collect the precipitate, wash it with ethanol twice, then wash it with water 3 times, and dry it at 45°C for 12 hours to obtain modified nano-hydroxyapatite loaded with an antibacterial agent; S2. Mix 10 parts by weight of the modified porous starch and 2 parts by weight of the antibacterial agent-loaded modified nano-hydroxyapatite prepared in step S1 with 100 parts by weight of water, and then stir the mixture at 40°C and 300 rpm for 3 hours, and then centrifuge at 4000 rpm for 5 minutes, collect the precipitate, wash it with water 3 times, and dry it at 45°C for 40 minutes to obtain a synergist.

[0029] The preparation method of the modified porous starch comprises the following steps: 1 part by weight of anhydrous sodium sulfate and 0.1 part by weight of sodium hydroxide were added to 100 parts by weight of water and mixed evenly, and then 5 parts by weight of porous starch and 0.4 parts by weight of benzyl iodide were added, and the mixture was stirred at 50°C for 3 hours; then the pH was adjusted to 6 with a 1 mol / L hydrochloric acid aqueous solution, filtered, the precipitate was collected, washed 3 times with water, and then washed 3 times with a 90wt% ethanol aqueous solution, and dried at 40°C for 10 hours to obtain modified porous starch.

[0030] Comparative Example 1 A method for preparing a flame-retardant ABS composite material for automobiles, which is different from Example 1 in that the method for preparing the synergist comprises the following steps: S1. Mix 5 parts by weight of nano-hydroxyapatite with 100 parts by weight of ethanol, and then ultrasonically treat for 30 minutes to obtain a suspension; add 2 parts by weight of lacquer phenol to the suspension, mix and stir at 70°C for 3 hours to obtain a mixed solution; centrifuge the mixed solution, collect the precipitate, wash it with ethanol 3 times, and dry it at 45°C for 5 hours to obtain modified nano-hydroxyapatite; then add 2 parts by weight of modified nano-hydroxyapatite to 50 parts by weight of a 1 g / L copper chloride aqueous solution, and add 0.03 parts by weight of anhydrous sodium acetate, and then mix and stir at 12 MPa and 90°C for 4 hours; centrifuge after cooling, collect the precipitate, wash it with ethanol twice, then wash it with water 3 times, and dry it at 45°C for 12 hours to obtain modified nano-hydroxyapatite loaded with an antibacterial agent; S2. Mix 10 parts by weight of the modified porous starch and 2 parts by weight of the antibacterial agent-loaded modified nano-hydroxyapatite prepared in step S1 with 100 parts by weight of water, and then stir the mixture at 40°C and 300 rpm for 3 hours, and then centrifuge at 4000 rpm for 5 minutes, collect the precipitate, wash it with water 3 times, and dry it at 45°C for 40 minutes to obtain a synergist.

[0031] The preparation method of the modified porous starch comprises the following steps: 1 part by weight of anhydrous sodium sulfate and 0.1 part by weight of sodium hydroxide were added to 100 parts by weight of water and mixed evenly, and then 5 parts by weight of porous starch and 0.4 parts by weight of methylbenzyl chloride were added, and the mixture was stirred at 50°C for 3 hours; then the pH was adjusted to 6 with a 1 mol / L hydrochloric acid aqueous solution, filtered, the precipitate was collected, washed 3 times with water, and then washed 3 times with a 90wt% ethanol aqueous solution, and dried at 40°C for 10 hours to obtain modified porous starch.

[0032] Comparative Example 2 A method for preparing a flame-retardant ABS composite material for automobiles, which is different from Example 1 in that the method for preparing the synergist comprises the following steps: S1. Mix 5 parts by weight of nano-hydroxyapatite with 100 parts by weight of ethanol, and then ultrasonically treat for 30 minutes to obtain a suspension; add 2 parts by weight of tannic acid to the suspension, mix and stir at 70°C for 3 hours to obtain a mixed solution; centrifuge the mixed solution, collect the precipitate, wash it with ethanol 3 times, and dry it at 45°C for 5 hours to obtain modified nano-hydroxyapatite; then add 2 parts by weight of modified nano-hydroxyapatite to 50 parts by weight of a 1 g / L copper chloride aqueous solution, and add 0.03 parts by weight of anhydrous sodium acetate, and then mix and stir at 12 MPa and 90°C for 4 hours; cool and centrifuge, collect the precipitate, wash it with ethanol 2 times, then wash it with water 3 times, and dry it at 45°C for 12 hours to obtain modified nano-hydroxyapatite loaded with an antibacterial agent; S2. Mix 10 parts by weight of the modified porous starch and 2 parts by weight of the antibacterial agent-loaded modified nano-hydroxyapatite prepared in step S1 with 100 parts by weight of water, and then stir the mixture at 40°C and 300 rpm for 3 hours, and then centrifuge at 4000 rpm for 5 minutes, collect the precipitate, wash it with water 3 times, and dry it at 45°C for 40 minutes to obtain a synergist.

[0033] The preparation method of the modified porous starch is consistent with that of Example 4.

[0034] Comparative Example 3 A method for preparing a flame-retardant ABS composite material for automobiles, which is different from Example 1 in that the method for preparing the synergist comprises the following steps: 5 parts by weight of nano-hydroxyapatite are mixed with 100 parts by weight of ethanol, and then ultrasonically treated for 30 minutes to obtain a suspension; 2 parts by weight of lacquer phenol are added to the suspension, mixed and stirred at 70°C for 3 hours to obtain a mixed solution; the mixed solution is centrifuged, the precipitate is collected, washed with ethanol 3 times, and dried at 45°C for 5 hours to obtain modified nano-hydroxyapatite; then 2 parts by weight of modified nano-hydroxyapatite are added to 50 parts by weight of a 1 g / L copper chloride aqueous solution, and 0.03 parts by weight of anhydrous sodium acetate are added, and then mixed and stirred at 12 MPa and 90°C for 4 hours; after cooling, centrifugation is performed, the precipitate is collected, washed with ethanol twice, washed with water 3 times, and dried at 45°C for 12 hours to obtain modified nano-hydroxyapatite loaded with an antibacterial agent, i.e., a synergist.

[0035] Comparative Example 4 A method for preparing a flame-retardant ABS composite material for automobiles, which is different from Example 1 in that the method for preparing the synergist comprises the following steps: Then, 2 parts by weight of nano-hydroxyapatite are added to 50 parts by weight of a 1 g / L copper chloride aqueous solution, and 0.03 parts by weight of anhydrous sodium acetate are added, followed by mixing and stirring at 12 MPa and 90°C for 4 hours; after cooling, the mixture is centrifuged, the precipitate is collected, washed twice with ethanol, then washed three times with water, and dried at 45°C for 12 hours to obtain nano-hydroxyapatite loaded with an antibacterial agent, i.e., a synergist.

[0036] Comparative Example 5 A method for preparing a flame-retardant ABS composite material for automobiles, which differs from Example 1 in that no synergist is added, namely: (1) 75 parts by weight of ABS resin, 8 parts by weight of bromotriazine, 2 parts by weight of pentaerythritol stearate, 3 parts by weight of auxiliary agent, 1.5 parts by weight of antioxidant 1010, and 4 parts by weight of silicon dioxide were mixed uniformly to obtain a mixture; then the mixture was added to an internal mixer at a mixing temperature of 120° C. for 25 minutes to obtain a premix; (2) The premix is ​​then fed into a twin-screw extruder for extrusion and granulation. The screw speed of the twin-screw extruder is 500 rpm and the barrel temperature is 190°C, thereby obtaining a flame-retardant ABS composite material for automobiles.

[0037] The auxiliary agent is prepared by mixing epoxy soybean oil and epoxy modified silicone oil in a mass ratio of 1:2.

[0038] Test Example 1 Performance Testing The ABS composite materials prepared in the examples and comparative examples were dried in a blast oven at 80°C for 4 hours, and then injection molded into standard specimens and standard square plates using a plastic injection molding machine at an injection molding temperature of 210°C; the injection molded specimens and square plates were placed at a relative humidity of 50% and 23°C for at least 24 hours before performance testing. The test method was carried out as follows: Combustion performance: The flame retardant grade of 1.6mm standard specimens was tested according to UL94-2009 standard; Contact angle: The injection molded square plate is tested by using the shape image analysis method and the angle measurement method; Izod notched impact strength: Injection molded into rod-shaped specimens that meet the requirements of ISO 180:2023 Izod notched impact strength test, and perform Izod notched impact strength test at 25°C with reference to ISO 180:2023 standard; UV aging resistance: wavelength is 340nm, irradiation intensity is 0.08W / m 2 The sample was irradiated with a deuterium lamp for 600 hours for UV aging, and then the notched cantilever beam impact strength of the sample after UV aging was tested again with reference to ISO 180:2023 standard. The loss rate of the notched cantilever beam impact strength of the sample before and after light aging was used to test its resistance to UV aging. The calculation formula for the loss rate of the notched cantilever beam impact strength is as follows: Loss rate (%) = (N0-N1) / N0×100% Where N0 is the notched cantilever beam impact strength before light aging (KJ / m 2 ); N1 is the cantilever beam notched impact strength after light aging (KJ / m 2 ); The test results are shown in Table 1: Table 1 It can be seen from Table 1 that the flame retardancy grades of the embodiments and comparative examples are all V-0, indicating that the ABS composite materials prepared by embodiments 1-4 and comparative examples 1-5 of the present invention all have good flame retardancy.

[0039] By comparing Examples 1-4 and Comparative Examples 1-5, it can be seen that the notched impact strength of the Izod beam of Examples 1-4 and Comparative Examples 1-3 is significantly higher than that of Comparative Examples 4-5, and the notched impact strength loss rate of the Izod beam after ultraviolet aging is significantly lower than that of Comparative Examples 4-5, indicating that the synergist introduced in Examples 1-4 and Comparative Examples 1-3 of the present invention is beneficial to improving the notched impact strength of the Izod beam and the resistance to ultraviolet aging of the ABS composite material. The notched impact strength of the Izod beam of Examples 2-4 and Comparative Example 1 is higher than that of Examples 1 and Comparative Examples 2-3, and the resistance to ultraviolet aging is better than that of Examples 1 and Comparative Examples 2-3. The reason may be that the modified porous starch is introduced during the preparation of the synergist of Examples 2-4 and Comparative Example 1. The porous structure of the modified porous starch can adsorb nanohydroxyapatite to prevent its agglomeration, and at the same time improve the compatibility between the modified nanohydroxyapatite loaded with the antibacterial agent and the ABS resin matrix. The uniformly dispersed synergist can more effectively play its reinforcing role in the ABS composite material, which is beneficial to improving the notched impact strength of the Izod beam of the ABS composite material. Since the chemical bonds (such as double bonds, etc.) in the ABS resin will undergo photo-oxidation reactions under ultraviolet irradiation, resulting in the breakage and cross-linking of the molecular chains, as the aging process proceeds, the structure of the material is destroyed, and cracks and powdering will appear on the surface, resulting in the cantilever beam notched impact strength. The introduction of benzyl groups into the modified porous starch absorbs the energy of ultraviolet rays, reduces the impact of ultraviolet rays on the ABS resin, and is beneficial to improving the anti-ultraviolet light aging performance of the ABS composite material. The cantilever beam notched impact strength of Example 2-4 is higher than that of Comparative Example 1, and the ultraviolet light aging resistance is better than that of Comparative Example 1. The reason for this may be that the larger chlorine, bromine, and iodine atoms in the modifiers 1,4-dichlorobenzyl, benzyl bromide, and benzyl iodine used in Examples 2-4 will increase the volume and structural complexity of the molecules in the modified starch molecules. When ultraviolet rays enter the ABS composite material, these larger atoms will cause more scattering and reflection of the light in the ABS composite material, increase the propagation path of ultraviolet rays in the ABS composite material, and increase the probability of ultraviolet rays being absorbed and scattered. The relatively small structure of methylbenzyl chloride has weaker scattering and reflection effects on light, and ultraviolet rays can more easily penetrate ABS composite materials, and its anti-ultraviolet light aging performance is poor.

[0040] By comparing Examples 1-4 and Comparative Examples 1-5, it can be seen that the contact angles of Examples 2-4 and Comparative Example 1 are significantly greater than those of Examples 1 and Comparative Examples 2-5, indicating that the synergist introduced in Examples 2-4 and Comparative Example 1 of the present invention is beneficial to improving the waterproof performance of the ABS composite material. The reason for this may be that in the preparation of the synergist, 1,4-dichlorobenzyl, benzyl bromide, benzyl iodide and p-methylbenzyl chloride are used as modifiers to modify the modified porous starch. When benzyl groups are introduced into starch molecules, the overall chemical structure of the starch changes, and a large number of hydroxyl groups in the original starch molecules are partially covered by the hydrophobic benzyl groups, which reduces the interaction between the starch molecules and the water molecules, thereby showing enhanced hydrophobicity.

[0041] By comparing Examples 2-4 and Comparative Example 1, it can be found that the contact angle of Examples 2-4 is greater than that of Comparative Example 1, and the contact angle of Example 4 is the largest, reaching 105°. The reason for this may be that under the same reaction conditions, the reactivity of the modifiers 1,4-dichlorobenzyl, benzyl bromide, and benzyl iodide used in Examples 2-4 is significantly better than that of p-methylbenzyl chloride. The leaving ability of chlorine, bromine, and iodine atoms in 1,4-dichlorobenzyl, benzyl bromide, and benzyl iodide is relatively strong, among which benzyl iodide is the strongest. Therefore, when reacting with starch, it is easier to undergo substitution reaction with the hydroxyl groups on the starch molecules, thereby more efficiently introducing hydrophobic groups into the starch molecules. The presence of methyl in p-methylbenzyl chloride may affect the leaving activity of chlorine atoms to a certain extent, resulting in relatively low reaction efficiency with starch, relatively small number of introduced hydrophobic groups, and less obvious improvement in hydrophobicity.

[0042] Comparing Example 1 and Comparative Examples 2-5, it is found that the contact angle of Comparative Example 5 without adding a synergist is >90°, showing good hydrophobicity, while the contact angles of Example 1 and Comparative Examples 2-4 with added synergists are ≤90°, and the hydrophobic performance is poor. The reason for this may be that the porous starch contained in the synergist in Example 1 is hydrophilic, resulting in a decrease in hydrophobicity; the tannic acid in Comparative Example 2 introduces hydrophilic phenolic hydroxyl groups, and the hydrophobicity is further reduced; the hydrophilic groups on the surface of the nanohydroxyapatite in Comparative Example 4 cause its hydrophobicity to decrease; and Comparative Example 3, because the hydrophilic groups of the nanohydroxyapatite modified by urushiol are replaced, and a long carbon chain with hydrophobicity is introduced, shows better hydrophobicity than Example 1, Comparative Example 2 and Comparative Example 4.

[0043] Test Example 2 Antibacterial performance test The flame-retardant ABS composite materials for automobiles prepared in Examples 1-4 of the present invention and Comparative Examples 1-5 were placed naturally at room temperature for 100 days, and then the antibacterial properties of the flame-retardant ABS composite materials for automobiles prepared in Examples 1-4 of the present invention and Comparative Examples 1-5 were tested according to the test method provided in the standard "GB / T 31402-2023 Determination of antibacterial activity on the surface of plastics and other non-porous materials"; experimental bacteria: Escherichia coli (commercially available, number: ATCC 8739), Staphylococcus aureus (commercially available, number: ATCC 6538P); The test results are shown in Table 2: Table 2 As shown in Table 2, the antibacterial performance test was carried out after the initial storage of up to 100 days before the test of each embodiment and comparative example. By comparing embodiments 1-4 and comparative examples 1-5, it can be found that the antibacterial rates of embodiments 1-4 and comparative examples 1-4 with the addition of synergist against Escherichia coli and Staphylococcus aureus are significantly higher than those of comparative example 5 without the addition of synergist. By comparing embodiments 1-4 and comparative examples 1-4, it can be found that the antibacterial rates of embodiments 2-4 and comparative example 1 against Escherichia coli and Staphylococcus aureus are slightly different, both reaching more than 99%, and the antibacterial rates are higher than those of embodiments 1 and comparative examples 2-4, indicating that the introduction of modified porous starch in the preparation process of the synergist is conducive to improving the antibacterial effect of the ABS composite material and can achieve long-term antibacterial.

[0044] Comparing Example 1 and Comparative Examples 2-4, it is found that the antibacterial rates of Example 1 and Comparative Example 2, in which porous starch is introduced during the preparation of the synergist, are higher than those of Comparative Examples 3-4. The reason for this may be that porous starch has excellent adsorption properties, and when combined with the modified nano-hydroxyapatite loaded with antibacterial agent, the antibacterial ions in the modified nano-hydroxyapatite can be fixed, and the antibacterial ions of the modified nano-hydroxyapatite can be prevented from precipitating, thereby improving the antibacterial properties. The antibacterial rate of Example 1 in which urushiol-modified nano-hydroxyapatite is higher than that of Comparative Example 2 in which tannic acid-modified nano-hydroxyapatite is used, and the reason for this may be that compared with tannic acid, urushiol contains unsaturated carbon long side chains, which can have good interfacial compatibility with the soft and hard segments of ABS resin. During the blending process, the double bonds of the unsaturated long side chains are opened, and a cross-linked interpenetrating network structure is formed with the ABS resin, which increases the compatibility of nano-hydroxyapatite with ABS resin, making it evenly dispersed in the ABS resin, which is beneficial to improving the antibacterial properties.

[0045] Comparing Comparative Example 3 and Comparative Example 4, it is found that the antibacterial rate of Comparative Example 3 using urushiol-modified nano-hydroxyapatite loaded with antibacterial agent as a synergist is higher than that of Comparative Example 4 using nano-hydroxyapatite loaded with antibacterial agent as a synergist. The reason may be that the urushiol-modified nano-hydroxyapatite is mixed with metal copper ions, and the urushiol modified on the nano-hydroxyapatite loads Cu through metal chelation coordination. 2+ , which enhances the copper ion loading capacity of nanohydroxyapatite, making the copper ion loading capacity of urushiol-modified nanohydroxyapatite higher than that of unmodified nanohydroxyapatite, thus improving the antibacterial performance. 2+ The strong coordination of ions makes most of the Cu 2+ The ions are anchored in the ABS composite material. Compared with nanohydroxyapatite, only a small amount of Cu 2+ Ions are dissolved from the surface of the ABS composite material, and the amount of dissolved metal ions is small, which is beneficial for the ABS composite material to maintain the antibacterial effect for a longer time.

Claims

1. A method for preparing a flame-retardant ABS composite material for automobiles, characterized in that: The following steps are involved: (1) Mix ABS resin, brominated flame retardant, lubricant, additive, antioxidant, silicon dioxide and synergist to obtain a mixture; then add the mixture into an internal mixer at a mixing temperature of 100-150° C. for 15-30 minutes to obtain a premix; (2) The premix is ​​then fed into a twin-screw extruder for extrusion and granulation. The screw speed of the twin-screw extruder is 300-800 rpm and the barrel temperature is 160-220° C., thereby obtaining a flame-retardant ABS composite material for automobiles.

2. The method for preparing the flame-retardant ABS composite material for automobiles according to claim 1, characterized in that: The weight proportion of each raw material component is: ABS resin 50-80 parts, brominated flame retardant 6-15 parts, silicon dioxide 3-5 parts, lubricant 1-3 parts, auxiliary agent 1-4 parts, synergist 4-7 parts, antioxidant 1-2 parts.

3. The method for preparing the flame-retardant ABS composite material for automobiles according to claim 1 or 2, characterized in that: The brominated flame retardant is selected from one or more of decabromodiphenylethane, brominated epoxy resin, tetrabromobisphenol A, and bromotriazine.

4. The method for preparing the flame-retardant ABS composite material for automobiles according to claim 1 or 2, characterized in that: The lubricant is selected from one or more of pentaerythritol stearate, paraffin, silicone powder, and ethylene bis stearamide; the auxiliary agent is prepared by mixing epoxy soybean oil and epoxy modified silicone oil in a mass ratio of 1:1-3.

5. The method for preparing the flame-retardant ABS composite material for automobiles according to claim 1 or 2, characterized in that: The antioxidant is selected from one or more of antioxidant 1076, antioxidant 1010, antioxidant 168, antioxidant 3114, and antioxidant 1098.

6. The method for preparing the flame-retardant ABS composite material for automobiles according to claim 1 or 2, characterized in that: The preparation method of the synergist comprises the following steps, calculated by weight: S1, mixing 4-6 parts of nano-hydroxyapatite with 95-105 parts of ethanol, and then ultrasonically treating for 20-40 minutes to obtain a suspension; 1-3 parts of lacquer phenol are added to the suspension, mixed and stirred at 65-75°C for 2-4h to obtain a mixed solution; the mixed solution is centrifuged, the precipitate is collected, washed with ethanol 2-3 times, and dried at 43-48°C for 3-6h to obtain modified nano-hydroxyapatite; then 1-3 parts of the modified nano-hydroxyapatite are added to 45-55 parts of a copper chloride aqueous solution with a concentration of 0.8-1.5g / L, and 0.01-0.05 parts of anhydrous sodium acetate are added, and then mixed and stirred at 10-20MPa and 80-100°C for 3-5h; after cooling, centrifugation is performed, the precipitate is collected, washed with ethanol 1-2 times, and then washed with water 2-3 times, and dried at 40-48°C for 8-15h to obtain modified nano-hydroxyapatite loaded with an antibacterial agent; S2. Mix 8-12 parts of starch additive and 1-3 parts of antibacterial agent-modified nano-hydroxyapatite prepared in step S1 with 95-105 parts of water, and then stir at 38-42° C. and 200-400 rpm for 2-4 hours, and then centrifuge at 2000-5000 rpm for 3-8 minutes, collect the precipitate, wash it with water 2-3 times, and dry it at 43-48° C. for 30-60 minutes to obtain a synergist.

7. The method for preparing the flame-retardant ABS composite material for automobiles according to claim 6, characterized in that: The starch additive in step S2 is selected from at least one of porous starch and modified porous starch.

8. The method for preparing the flame-retardant ABS composite material for automobiles according to claim 7, characterized in that: The preparation method of the modified porous starch comprises the following steps, measured by weight: 0.5-1.5 parts of anhydrous sodium sulfate and 0.05-0.2 parts of sodium hydroxide are added to 95-105 parts of water and mixed evenly, then 4.5-5.5 parts of porous starch and 0.3-0.5 parts of modifier are added, and the mixture is stirred at 40-60°C for 2-5 hours; then the pH value is adjusted to 5.8-6.2 with 0.5-1 mol / L hydrochloric acid aqueous solution, filtered, the precipitate is collected, washed with water for 2-3 times, and then washed with 90-95wt% ethanol aqueous solution for 2-3 times, and dried at 38-45°C for 8-12 hours to obtain modified porous starch.

9. The method for preparing a flame-retardant ABS composite material for automobiles according to claim 8, characterized in that: The modifier is selected from benzyl iodide, benzyl bromide, and 1,4-dichlorobenzyl.

10. A flame-retardant ABS composite material for automobiles, characterized in that: The method is prepared by any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of high flame retardant ABS automotive interior trim

    CN106589771A

  • Flame-retardant ABS resin with excellent performance and preparation method thereof

    CN104479238A

  • High-efficiency improved ABS (Acrylonitrile Butadiene Styrene) composite material for loading composite flame retardant by using nano-hydroxyapatite and preparation method thereof

    CN104845025A

  • Environment-friendly and antibacterial plastic for interior and exterior decoration of automobile and preparation method of environment-friendly and antibacterial plastic

    CN106188644A

  • Antifouling paint based on urushiol copper polymer and preparation method of antifouling paint

    CN108641597A